PELATIHAN KULTUR JARINGAN TUMBUHAN BAGI SISWA SMA NEGERI 7 YOGYAKARTA - None, Ratih Restiani; Ariestanti, Catarina Aprilia; Purba, Laurentia Henrieta Permita Sari; Retnowati, Theresia Sri; Matheos, Josiah Herald; Kaban, Sarah Mega Pratenna; Sekar, Astrid Ayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2023)
Plant tissue culture is one of the topics in the Biotechnology module of Biology for senior high school class XII. This topic has not been optimally provided in schools, especially in SMA Negeri 7 Yogyakarta due to the limited human resources who are experienced in plant tissue culture and the unavailability of facilities and equipment that support the implementation of the practicum topic. Therefore, this workshop aimed to help students gain knowledge and skills regarding the basic principles, benefits, and stages of plant tissue culture. The workshop was conducted in the Biology Laboratory of SMA Negeri 7 Yogyakarta and participated by 10 class XII students. The workshop consisted of questions and answers before the workshop, materials explanation, hands-on activities, questions and answers after the workshop, and evaluation. The material was delivered using lecturing methods and interactive discussions, followed by practical activities including preparation of culture media, sterilization and inoculation of explants and acclimatization which were carried out by engaging the active participation of each student. The results obtained in this workshop were that students were able to understand and implement plant tissue culture practical activities as well.